KERJASAMA ANTAR NEGARA DALAM MENGIDENTIFIKASI PESAWAT UDARA GUNA MENDUKUNG PENGAMANAN WILAYAH UDARA NASIONAL INDONESIA (Universitas Perrtahanan Indonesia (UNHAN), 2023)
Cooperation between countries in securing the national airspace of Indonesia is still not optimal, because there are still violations for various reasons related to flight permits, FIR control in the Riau Islands, the perspective of jurisdictional airspace (EEZ) and ASLs. The purpose of this study is to analyze the mechanism of cooperation between countries in identifying aircraft and analyzing the impact of such cooperation on violations of Indonesia’s national airspace. The study uses a qualitative method with a narrative design. Data were obtained by interview and observation techniques on the actors in the field. The results of the study show that cooperation between countries can be carried out in the form of multilateral cooperation in the form of violation prevention mechanisms under the auspices of the international organization ICAO or in the form of bilateral cooperation in the form of CMAC implementation between Indonesia - Singapore and Joint Integrated Exercise between Indonesia - US in EEZ and ASLs. The cooperation mechanism generally has an impact on reducing the intensity of violations that occur in Indonesia’s national airspace. The conclusion of this study states that cooperation between countries in identifying aircraft will have an impact on reducing violations of Indonesia’s national airspace.